Assessing Oral Health-Related Quality of Life (OHRQoL) Using the Oral Health Impact Profile (OHIP-14) among the Prisoners in the Central Jail in Vidarbha Region of Maharashtra, India: A Cross-Sectional Study - Manish B. Shrigiriwar; Neelam D. Chandwani; Unnati Gedam; PN Ramaraj; Ranjana Deshmukh; Anjali Gayke (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: The prison population is a physically, mentally, socially, and economically vulnerable sector in our society with neglected oral health. Dental check-ups not only provide the necessity of treatment but also create awareness regarding the importance of oral health among the incarcerated individuals. Aim: The study aims to evaluate the oral health status and its impact on oral health-related quality of life (OHRQoL) among the prisoners through the application of the oral health impact profile (OHIP-14). Methodology: A cross-sectional study design involved demographic details, oral examination to assess DMFT index, and structured OHIP-14 questionnaire to assess seven dimensions of the oral health impact profile of 440 male inmates. The responses were recorded in a five-point Likert scale from 0 to 4. The final score was calculated. Results: The overall mean OHIP score was 14.048 with a standard deviation of 9.995. Out of seven, the most affected domain was psychological discomfort (mean 2.49, SD 1.68) and the least affected domain was functional disability (mean 1.21, SD 1.18). Conclusion: The findings from this research can contribute valuable insights into the oral health challenges faced by incarcerated individuals, potentially guiding the development of targeted oral health interventions within correctional settings.